2004
DOI: 10.1242/jeb.01208
|View full text |Cite
|
Sign up to set email alerts
|

The anterior stomach of larval mosquitoes (Aedes aegypti):effects of neuropeptides on transepithelial ion transport and muscular motility

Abstract: SUMMARY The present investigation studied the influence of a number of neuropeptides on semi-open preparations of the isolated and perfused anterior stomach of larval Aedes aegypti. Effects of peptides were observed on the lumen negative transepithelial voltage (Vte) that is present with serotonin in the bath; this voltage most likely reflects active HCO3– secretion involved in alkalization of the larval anterior stomach. The five different A. aegypti allatostatins(allatostatin A 1–5) all affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 43 publications
2
55
0
Order By: Relevance
“…In the cockroach, ASTs have been shown to decrease food consumption (Aguilar et al, 2003). There is increasing evidence that ASTs modulate ion transport of various regions of the gut (Onken et al, 2004;Vanderveken and O'Donnell, 2014). An important group of insects in which ASTs have not been studied are the midges.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…In the cockroach, ASTs have been shown to decrease food consumption (Aguilar et al, 2003). There is increasing evidence that ASTs modulate ion transport of various regions of the gut (Onken et al, 2004;Vanderveken and O'Donnell, 2014). An important group of insects in which ASTs have not been studied are the midges.…”
Section: Research Articlementioning
confidence: 99%
“…Studies have shown that AST modulates gut muscle activity (Sarkar et al, 2003;Duve et al, 2000). Studies have also provided evidence that AST directly modulates ion transport activities in gut epithelia (Onken et al, 2004;Vanderveken and O'Donnell, 2014). By simultaneously and perhaps independently modulating transit time of hindgut luminal contents and the magnitude of epithelial ion reabsorption through direct neural control, the midge would greatly increase its ability to fine-tune the reabsorptive and excretory functions of the hindgut.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that FGLa/ASTs can affect both muscle contractility and reabsorption because FGLa/ASTs have been shown to alter ion transport in other insect species (Onken et al, 2004). Future work will examine the role that FGLa/ASTs play in locust gut ion transport to further elucidate the physiological roles that this peptide family plays in digestion.…”
Section: The Journal Of Experimental Biology 215 (19)mentioning
confidence: 99%
“…The present studies of the structure and ultrastructure of the muscularis of this organ in the 2 nd , 3 rd and 4 th larval instars were prompted by our interest in understanding the mechanisms by which the multiple functions of the midgut are controlled and integrated by neurotransmitters and hormones. Previously, we had found that both alkali secretion and motility of the isolated, perfused anterior stomach were stimulated by serotonin (Clark et al, 2000;Onken et al, 2004;Onken et al, 2004a), and that the midgut receives an extensive serotonergic innervation that is derived from a small number of bilateral neurons (Moffett & Moffett, 2005). Several Aedes neuropeptides were found to have inhibitory effects on motility, ion transport, or both functions (Onken et al 2004a), and these effects may be reflected by an apparent peptidergic innervation of the gut and by the presence of a substantial population of enteroendocrine cells (Moffett & Moffett, 2005).…”
Section: Introductionmentioning
confidence: 99%